2013
DOI: 10.1097/pcc.0b013e31825b54ae
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural Hearing Loss and Language Development Following Neonatal Extracorporeal Membrane Oxygenation

Abstract: OBJECTIVE:To determine the prevalence of hearing loss in school-age children who have undergone neonatal extracorporeal membrane oxygenation (ECMO) treatment and to identify any effects of hearing loss on speech-and language development. DESIGN:Prospective longitudinal follow-up study within the framework of a structured post-ECMO follow-up program.SETTING: Outpatient clinic of a level III university hospital. RESULTS:Tone audiometry was performed by standardized protocol in 136 children aged 5 to 12 years. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Using the current guidelines, neonatal ECMO survivors at risk for school problems will not be identified. 6,7,[25][26][27] We therefore propose a problemoriented revision of follow-up protocols. persist even into adolescence, 2 -4 neuropsychological follow-up that extends beyond the age of 5 years is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Using the current guidelines, neonatal ECMO survivors at risk for school problems will not be identified. 6,7,[25][26][27] We therefore propose a problemoriented revision of follow-up protocols. persist even into adolescence, 2 -4 neuropsychological follow-up that extends beyond the age of 5 years is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies concluded that global ability of former ECMO patients was not severely affected, with mean scores for the ECMO patients falling within 1 SD of the population mean (5, 6, 11, 15, 17, 19, 24, 26, 27, 29, 3436, 55, 58). Four studies demonstrated mean scores for cognitive ability <80 (population mean, 100, SD, 15) (13, 16, 49, 51).…”
Section: Resultsmentioning
confidence: 99%
“…The neurological long-term outcome of children with congenital renal failure has not yet been studied prospectively, but it seems to be appropriate for age in most patients [ 2 ]. In a prospective follow-up study by van den Hondel et al [ 17 ], 24.3% of the ECMO survivors had hearing loss, but they showed normal intelligence scores and language skills at the age of 5 years. Several long-term outcome studies on children with congenital renal failure have been done with a focus on renal outcome and general survival, not taking into account the possibility of ECMO support.…”
Section: Discussionmentioning
confidence: 99%